A) (2x+2y) - (x+y) + (x-2y) dla x=0,5 i y=-1
b) (2a-3b) - (-5a+4b) dla a =1/7 i b= -2
c) (2x do potęgi drugiej - 4y) - (9xdo potęgi drugiej + 6y) + (2xdo potęgi drugiej + y) dla x=0,2 i y=-1/3
d) 5a- [3a do potęgi drugiej+4a-(-3a+4a)] dla a=-1/2

1

Odpowiedzi

2010-02-08T16:18:47+01:00
A) (2x+2y) - (x+y) + (x-2y) dla x=0,5 i y=-1
= 2x +2y -x -y + x -2y =
= 2x -y
= 2*(0,5) - (-1)=
= 1 + 1 =
= 2
b) (2a-3b) - (-5a+4b) dla a =1/7 i b= -2
= 2a - 3b +5a -4b =
= 7a - 7b=
= 7( a -b)
= 7*[1/7 - (-2)]=
= 7*[1/7 + 2]=
= 7*(15/7) =
= 15
c) (2x do potęgi drugiej - 4y) - (9xdo potęgi drugiej + 6y) + (2xdo potęgi drugiej + y) dla x=0,2 i y=-1/3
(2x² -4y) -(9x²+ 6y) + (2x² + y)=
= 2x² -4y -9x² -6y + 2x² +y =
= -5x² -9 y
=(-5)*(0,2)² -9*(-1/3)=
= (-5)*0,04 + 3 =
= - 0,2 + 3=
= 2,8
d) 5a- [3a do potęgi drugiej+4a-(-3a+4a)] dla a=-1/2
= 5a -[ 3a² + 4a -( -3a + 4a)] =
= 5a [ 3a² + 4a + 3a -4a] =
= 5a [ 3a² + 3a ]=
= 5a*3a( a + 1 )=
= 15a² ( a + 1)

= 15*(-1/2)² ( -1/2 + 1)=
= 15* 1/4*( 1/2)=
= 15*1/8=
= 15/8